Growth differentiation factor‐15 and the risk of cardiovascular diseases and all‐cause mortality: A meta‐analysis of prospective studies - Xie, Shanhui; Lu, Liping; Liu, Liwei (Clinical cardiology (Mahwah, N.J.), 2019)
Background and Aim Previous studies have documented that the association between growth differentiation factor‐15 (GDF‐15) the risk of patients with cardiovascular diseases (CVDs). In this meta‐analysis, our main objective is to explore the associations between GDF‐15 and the risk of CVD or all‐cause mortality. Methods PubMed and ISI Web of Science (up to January 2018) electronic databases were browsed for eligible studies. The studies provided relevant data depicted as hazard ratio (HR) with 95% confidence interval (CI), with regard to the association between GDF‐15 levels and subsequent risk of CVDs or all‐cause mortality. A random‐effect model was applied to pool the HR and 95% CI. Results Thirty‐one prospective studies met the eligibility criteria involving 53 706 subjects with 7020 adverse outcome events. It was concluded that GDF‐15 levels were associated with an incremental risk of CVDs or all‐cause mortality. Highest GDF‐15 category was associated with greater risk of cardiovascular mortality (HR, 2.66; 95% CI, 1.69‐3.63), all‐cause mortality (HR, 2.52; 95% CI, 2.06‐2.97), and complex adverse outcome (HR, 1.81; 95% CI, 1.42‐2.21). As each log‐unit increment in GDF‐15 concentration, the corresponding risk of adverse events also escalated, cardiovascular mortality (HR, 2.11; 95% CI, 1.57‐2.66), all‐cause mortality (HR, 2.70; 95% CI, 2.29‐3.12), and complex adverse outcome (HR, 1.96; 95% CI, 1.64‐2.29). Conclusions Judging from the results of the data analysis, GDF‐15 levels may increase the risk of CVDs or all‐cause mortality.